Comparing Al-Faruqi's Concept of Islamization of Science with Kuntowijoyo's Prophetic Social Science - Fahmi Syaefudin (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
Muslims are faced with a time when the West dominates science. Muslims are shackled with the science of turats and irrationality inherent in every Islamic circle. That makes Islamic science stagnate and seem left far behind the Western world. This literature research collects data from various books and media to serve as a study's discussion source. The discussion begins by explaining Ismail Raji Al-Faruqi's concept of thinking about the Islamization of Science, then proceeds with Kuntowijoyo's Concept of Prophetic Social Science and draws a common thread between the two thoughts. The conclusion is that both have the same concentration in addressing the waves of modern science to be given a value following Islam.